99mTc-Labelled Anti NCA-95 Antibodies in Prosthetic Heart Valve Endocarditis - Bair, H.-J.; Becker, W.; Volkholz, H.-J.; Wolf, F. (Nuklearmedizin - NuclearMedicine, 1991)
A 54-y old women with earlier replacement of the mitral and aortic valves and clinical signs of localized endocarditis was studied with 99mTc-labelled anti NCA-95 antibody. Whereas echocardiographic findings were negative, increased radionuclide uptake was observed left parasternal over the mitral valve as a sign of prosthetic valve endocarditis. This result could be confirmed by a similar study with leukocytes labelled in vitro with 111ln-oxine.